Prion infections and anti-PrP antibodies trigger converging neurotoxic pathways - Herrmann, U. S.; Sonati, T.; Falsig, J.; Reimann, R. R.; Dametto, P.; O'Connor, T.; Li, B.; Lau, A.; Hornemann, S.; Sorce, S.; Wagner, U.; Sanoudou, D.; et al. (PLoS PathogPLoS PathogPLoS Pathog, 2015)
Prions induce lethal neurodegeneration and consist of PrPSc, an aggregated conformer of the cellular prion protein PrPC. Antibody-derived ligands to the globular domain of PrPC (collectively termed GDL) are also neurotoxic. Here we show that GDL and prion infections activate the same pathways. Firstly, both GDL and prion infection of cerebellar organotypic cultured slices (COCS) induced the production of reactive oxygen species (ROS). Accordingly, ROS scavenging, which counteracts GDL toxicity in vitro and in vivo, prolonged the lifespan of prion-infected mice and protected prion-infected COCS from neurodegeneration. Instead, neither glutamate receptor antagonists nor inhibitors of endoplasmic reticulum calcium channels abolished neurotoxicity in either model. Secondly, antibodies against the flexible tail (FT) of PrPC reduced neurotoxicity in both GDL-exposed and prion-infected COCS, suggesting that the FT executes toxicity in both paradigms. Thirdly, the PERK pathway of the unfolded protein response was activated in both models. Finally, 80% of transcriptionally downregulated genes overlapped between prion-infected and GDL-treated COCS. We conclude that GDL mimic the interaction of PrPSc with PrPC, thereby triggering the downstream events characteristic of prion infection.
Herrmann, Uli SSonati, TizianaFalsig, JeppeReimann, Regina RDametto, PaoloO'Connor, TracyLi, BeiLau, AgnesHornemann, SimoneSorce, SilviaWagner, UliSanoudou, DespinaAguzzi, AdrianoengResearch Support, Non-U.S. Gov't2015/02/25 06:00PLoS Pathog. 2015 Feb 24;11(2):e1004662. doi: 10.1371/journal.ppat.1004662. eCollection 2015 Feb.
Keywords: *Antibodies/immunology/toxicity; Animals; eIF-2 Kinase/genetics/immunology; Mice; Mice, Transgenic; Prion Diseases/*chemically induced/genetics/*immunology/pathology; PrPSc Proteins/genetics/*immunology; Reactive Oxygen Species/immunology; Signal Transduction/*drug effects/genetics/*immunology